Modern learning paradigms: A bibliometric analysis of augmented reality and virtual reality in vocational education - Fortuna, Aprilla; Prasetya, Febri; García, Juan Luis Cabanillas; Arcelus-Ulibarrena, Juana Maria; Salman, Amna; Karimi, Amir; Yusuf, Ahmad (Jurnal Pendidikan Teknologi Kejuruan, 2024)
This bibliometric analysis aimed to explore the publication trends of the last decade, especially on modern learning paradigms, focusing on implementing Augmented Reality and Virtual Reality in vocational education. This research specifically addressed the analysis of current technology trends, gaps, challenges, strengths, and opportunities of AR and VR during 2015-2024. This research method used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) procedures to collect data from publications focusing on high-quality research results. The data were analyzed and identified using MS Excel software and VOSviewer to visualize various critical metadata obtained in the Scopus database. Notably, publication trends and distribution patterns, the contributions of authors, the geographical spread of publications, and the identification of significant publication sources were all essentials for analyzing the opportunities and challenges within the context of vocational education. The results of this study identified an augmenting growth of publication trends from 2015-2023, including the country of origin of prominent authors such as Bacca et al. (Spain), Babu et al. (India), and Lerner et al. (Germany), whose research results have been proven to impact the primary reference in the field of vocational education in the utilization of AR and VR. They are widely cited and have become the primary references for other authors. Consequently, this bibliometric-based research underscores the potential of AR and VR technologies to improve vocational education by enhancing motivation, educational access, personalized learning, collaboration, and reducing operational costs.